Articulation disorders - Bernthal, John E. 4 0 16; Bankson, Nicholas W.; 5 (Englewood Cliffs, N.J. : Prentice-Hall, 1981)
An integrated and cohesive collection of information of the literature available on communication disorders.
Normal aspects of articulation -- Phonological development -- Factors related to articulatory disorders -- Articulatory assessment -- Remediation of articulatory disorders.
Includes bibliographies and indexes.
Keywords: 2 -- 0; 6; Articulation disorders.;Speech disorders; 20; 2